PENGARUH EDUKASI SEKS MELALUI APLIKASI VIDEO ANIMASI TERHADAP PENGETAHUAN DALAM MENCEGAH PELECEHAN SEKSUAL DI SDN 04 LUBUK DALAM KABUPATEN SIAK - Rummy Islami Zalni; Riska Mardianti; Melia Aprina; Ratna Juwita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Based on data from UPT P2TP2A Riau Province 2021, sexual crime cases handled by UPT P2TP2A Riau Province in the last 3 years from 2016 to 2018 there were 49 cases of sexual crimes against women and children in Pekanbaru city which shows that in 2016 there were 11 cases, then 2017 there were 18 cases, and in 2018 it again increased by 20 cases of sexual crimes . Providing sexual education at an early age will have an impact on children's sexual health as adults . The way to prevent sexual harassment is by providing education through animated media. Animation media is the movement of an object or image so that it can change position. The purpose of this study was to determine the effect of sex education through the application of animated videos on knowledge in preventing sexual harassment from an early age . This study used the One Group Pretest Posttest design . Data collection was carried out using a questionnaire sheet . The sample was determined by the total sampling method of 35 respondents. The results of the T-test test have a p-value of 0.000 because the value of 0.000 is less than 0.05, so it can be concluded that there is an effect of sex education through animated video applications on knowledge in preventing sexual harassment at SDN 04 Lubuk Dalam Siak Regency so that H0 is rejected . It is recommended that everyone use the animated video to increase knowledge in preventing sexual harassmentKeywords :animated video, knowledge, sexual harassment